Personal performative narrative as inquiry: speaking truth to social injustice in Cameroon - Alain, N J I (My University, 2012)
This practice-based research report reflects my analysis; exploration; interrogation and representation of social injustice in Cameroon as a lived experience. It is a personal narrative in performative approach that brings to the forefront the unspoken part of the country’s politics. It is an autobiographical account of the researcher-practitioner’s lived experiences. The primary source of material used in workshopping the piece is my autobiographical memories of the events that have constructed my socio-political identity so far.
M.A. University of the Witwatersrand, Faculty of Humanities (Dramatic Art), 2012